2021
DOI: 10.14712/18059694.2022.3
|View full text |Cite
|
Sign up to set email alerts
|

Goeckerman Regimen Reduces Alarmin Levels and PASI Score in Paediatric Patients with Psoriasis

Abstract: Background. Psoriasis is a chronic systemic inflammatory disease with (extra-)cutaneous manifestations. Inflammation is associated with cellular stress and tissue damage which lead to the release of alarmins (signals of danger). Goeckerman regimen (GR) is a highly efficacious treatment consisting of the application of pharmaceutical crude tar and UVB light exposure. The reduction of inflammatory processes in the skin is accompanied by changes in the levels of inflammatory markers - alarmins (HMBG-1, S100A7, S1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 60 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…The authors revealed that this caused a rapid decrease in S100A7 and S100A12 [182]. In another study, administering the previously mentioned GR regimen resulted in a significant drop in S100A7 and S100A9 [171]. Kruger et al observed that treatment with the anti-IL-17a agent secukinumab decreased the expression of S100 proteins, further confirming the influence of IL-17 on the S100 protein family [172,183].…”
Section: S100 Proteinsmentioning
confidence: 86%
See 2 more Smart Citations
“…The authors revealed that this caused a rapid decrease in S100A7 and S100A12 [182]. In another study, administering the previously mentioned GR regimen resulted in a significant drop in S100A7 and S100A9 [171]. Kruger et al observed that treatment with the anti-IL-17a agent secukinumab decreased the expression of S100 proteins, further confirming the influence of IL-17 on the S100 protein family [172,183].…”
Section: S100 Proteinsmentioning
confidence: 86%
“…One study examined the level of alarmins after anti-psoriatic therapy in pediatric patients who underwent the Goeckerman regimen (GR), which consists of applying pharmaceutical crude tar and UVB light exposure. Administering GR resulted in a significant drop in HMGB1, together with a reduction in the PASI score [171].…”
Section: S100 Proteinsmentioning
confidence: 94%
See 1 more Smart Citation